Analisis Faktor-Faktor Media Sosial Yang Mempengaruhi Keputusan Pembelian di Tuminis Catering Gresik - Ningrum, Ajeng Puspa; Hidayat, M. Syamsul; Kasnowo, Kasnowo (CV. Kalimasada Group, 2025)
Gresik Regency is one of the cities that has experienced significant development of the culinary sector. This is supported by an increase in the number of industrial workers who become potential markets. However, in the midst of increasingly fierce competition, culinary businesses are faced with challenges to innovate, especially in marketing strategies. This study aims to determine and describe the factors that influence purchasing decisions at Tuminis Catering in Gresik. The method used in this research is quantitative method. Determination of the sample using Non-Probability Sampling Technique and the number of samples was 110 samples. While the data analysis techniques used are validity tests, reliability tests. Based on the results of the study, it shows that indicators such as ordering information in captions and videos, bio links, frequency and consistency of uploads, testimonials, admin responses, and interactive features such as polls and QnA. This factor shows that the quality of communication and easy access to information on social media play an important role in influencing consumer purchasing decisions. Indicators such as image display, visual design variations, narration or voice over, to background music. This shows that social media that presents content with high aesthetic appeal can form positive perceptions and increase consumer buying interest.